Inverse eigenvalue problems for nonlocal Sturm-Liouville operators - Nizhnik, L. P. (Methods of Functional Analysis and Topology, 2009)
We solve the inverse spectral problem for a class of Sturm-Liouville operators with singular nonlocal potentials and nonlocal boundary conditions.